Development of Direct Aromatic Coupling Reactions by Transition-Metal Catalysis - Miura, Masahiro; Satoh, Tetsuya; Hirano, Koji (Bulletin of the Chemical Society of Japan, 2014)
Transition-metal-catalyzed aromatic cross-coupling reactions are highly useful for constructing various organic fine chemicals. The conventional methods, however, usually require the preactivation of aromatic substrates such as stoichiometric halogenation and metalation before the coupling event, which increases the steps leading to target molecules and yields inevitable salts as by-products. In order to cope with these problems, catalytic C–H transformation reactions on aromatic substrates have been one of the most intensive subjects in the area of catalytic organic synthesis. Summarized herein are our efforts for developing direct aromatic and heteroaromatic coupling reactions by using a number of transition metals as catalysts.